Immunological Changes of Basophil Hyperreactivity to Sweat in Patients With Well-Controlled Atopic Dermatitis - Numata, Tomofumi; Takahagi, Shunsuke; Ishii, Kaori; Morioke, Satoshi; Kan, Takanobu; Mizuno, Hayato; Yanase, Yuhki; Kawaguchi, Tomoko; Tanaka, Akio; Hide, Michihiro (Frontiers in Immunology, 2022)
Background: Sweat aggravates atopic dermatitis (AD). In patients with AD, type-I hypersensitivity to sweat may be shown by histamine release from patients’ basophils in response to the semi-purified sweat antigen (QR), and the presence of specific IgE binding to MGL_1304, the component of QR. However, there has been no information on immunological changes of type-I hypersensitivity to the sweat antigen in patients with well-controlled AD using topical corticosteroids (TCS) and/or biologics as treatments. Methods: Histamine-releasing tests using patients’ basophils and QR, and detection of serum IgE against MGL_1304 and mite allergen Der f 1 were performed in patients with AD who were well-controlled by topical TCS with/without dupilumab for 53-96 weeks. Results: In total, 14 patients were enrolled. Seven patients received TCS therapy alone (TCS group), and seven patients received TCS with dupilumab therapy (Dupilumab group). In all participants, the level of specific IgE against MGL_1304 decreased after treatments, but histamine release from basophils in response to QR did not show a statistically significant reduction; rather it increased. In the Dupilumab group, all changes in histamine release induced by QR (increase), IgE level against MGL_1304 (decrease) and that against Der f 1 (decrease) were statistically significant, whereas the TCS group showed no significant change in any of them. Conclusion: The well-controlled condition for 53-96 weeks resulted in no reduction of the hyperreactivity of basophils against sweat antigen in patients with AD, even with the treatment with dupilumab. This study suggests persistent basophil hyperreactivity to sweat antigen over a year or longer.